Quantification of DNA through the NanoDrop Spectrophotometer: Methodological Validation Using Standard Reference Material and Sprague Dawley Rat and Human DNA - Alejandro Monserrat García-Alegría; Iván Anduro-Corona; Cinthia Jhovanna Pérez-Martínez; María Alba Guadalupe Corella-Madueño; María Lucila Rascón-Durán; Humberto Astiazaran-Garcia (International Journal of Analytical Chemistry)
This study aimed to validate an analytical method to determine DNA concentration using standard reference material (NIST SRM 2372) and Sprague Dawley rat and human DNA. Microvolumes were used to analyse DNA samples. Linearity showed correlation coefficients higher than R ≥ 0.9950, and the precision value was ≤2% CV. Trueness based on bias and the percentage of recovery showed bias values lower than Z-test with a 95% confidence level and a recovery percentage within the range (% Rec = 100% ± 5%), and the stability of the samples was 60 days (2–4°C).